Knowledge of High School Students and Parents about Adolescent Reproductive Health - Ulfa Maihardi Putri; Elsa Yuniarti; Sa'adiatul Fuadiyah; Rahmawati D Rahmawati D (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Adolescent reproductive health knowledge at this time is not optimal. Based on observations at SMAN 1 Batang Anai, students' knowledge is limited to bathing regularly, exchanging underwear after bathing and for women changing pads only 3 times a day. besides,there are cases of premarital pregnancy and students who are suspected of liking the same sex. These cases is inseparable from parental supervision of adolescent attitudes and behavior that are  harm for adolescent reproductive health. The purpose of this study is to describe the knowledge of high school students and parents about adolescent reproductive health at SMAN 1 Batang Anai. This research is a descriptive study with  118 students  as populations and 24 students’ parents which are determined by propotionate stratified random sampling, and also test is given to measure their knowledge. this research uses simple regression analysis and path analysis. Generally the result shows that students’ and parents’ knowledge are enough, based on age, gender and majors of students’ majors as well as the level of education of parents including physical changes in adolescents 73.72%, maintaining adolescent reproductive health 53.51%, causes and effects from disorders and reproductive disorders 68.64% and PMS  and modes of transmission 64.19%. However, parents’ knowledge about maintaining reproductive health are less with 40.17%. Based on the data, it can be concluded that the knowledge of students and parents at SMAN 1 Batang Anai is not optimal.